THE INFLUENCE OF STORE ATMOSPHERE AND LOCATION ON PURCHASE DECISION AT PUSRI MART SEMARANG AREA - Ayu Sa’idah; Suryadi Poerbo; Fatchun Hasyim (Politeknik Negeri Semarang, 2019)
The purpose of this study areanalize the influence of store atmosphere and location on purchase decision at Pusri Mart area Semarang. The data collection technique are questionnaires, interview, observation, and literature study method. The number of samples in this study were 75 respondents and it was selected by incidental sampling technique. The data analysis technique is carried out by using classic assumption test (Normality test, Multicolinearity test, and Heteroscedasticity test), multiple linear regression analysis, model feasibility test, hypothesis test, Coefficient Correlation R, and Multiple Determination Coefficient (R2). The result of the research shows that: (1) store atmosphere (X1) has significant influence to the purchase decision on Pusri Mart area Semarang; (2) Location (X2) has significant influence to the purchasie decision on Pusri Mart area Semarang; (3) Store atmosphere is the variable which has the most dominant influence to the purchase decision on Pusri Mart area Semarang